Primary care for tinnitus: practice and opinion among GPs in England - El-Shunnar, Suliman K (Blackwell Publishing Ltd, 2011)
RATIONALE, AIM AND OBJECTIVE: Effective tinnitus management starts with appropriate general practitioner (GP) triage, which in England can be guided by the Department of Health's Good Practice Guide (GPG). Despite the prevalence of the condition, there has never been a systematic survey of its management in primary care in England. We aimed to evaluate how people with tinnitus are assessed and managed in general practice, noting variation in practice across GPs and health authorities, and evaluating how closely typical practice aligns to the GPG for tinnitus. METHODS: A nine-item postal questionnaire was sent to 2000 GPs randomly selected to proportionally represent the number of primary care trusts and strategic health authorities in England. RESULTS: We received 368 responses. Responses indicated a mix of frequent and infrequent practices, for example, 90% of GPs assessed the impact of tinnitus on quality of life, but fewer examined cranial nerves (38%) or assessed for a carotid bruit (26%) during a tinnitus consultation. In the management of tinnitus, 83% routinely removed earwax, and 87% provided information-based advice. In contrast, only 4% of responders would offer antidepressant drugs or psychological therapies. Thematic analysis revealed a desire for concise training on tinnitus management. CONCLUSIONS: GP assessment and management of tinnitus represents potential inequity of service for tinnitus patients. While the GPG aims to promote equity of care, it is only referred to by a minority of clinicians and so its utility for guiding service delivery is questionable. Although some GPs highlighted little demand for tinnitus management within their practice, many others expressed an unmet need for specific and concise GP training on tinnitus management. Further work should therefore evaluate current informational resources and propose effective modes of delivering educational updates.